Effizienz Deutscher Krankenhäuser im Zeitablauf - Schmitz, Hendrik; Augurzky, B.

Hochschulforscher oder Hochschullehrer? Eine Panel-Daten-Analyse wirtschaftswissenschaftlicher Bachelor- und Masterkurse - Lück, Sonja (Hochschulmanagement)

Monotonicity and Nash implementation in matching markets with contracts - Haake, Claus-Jochen; Klaus, Bettina (Economic Theory)

DIVIDING BY DEMANDING: OBJECT DIVISION THROUGH MARKET PROCEDURES - Haake, Claus-Jochen (International Game Theory Review)
We discuss a model, in which two agents may distribute finitely many objects among themselves. The conflict is resolved by means of a market procedure. Depending on the specifications, this procedure serves to achieve bargaining solutions such as the discrete Raiffa solution, the Kalai-Smorodinsky solution and the Perles-Maschler solution. The latter is axiomatized using the superadditivity axiom, which in the present context is readily interpreted as resolving a specific source of conflict potential.

Linkages between Financial Deepening, Trade Openness and Economic Development: Causality Evidence from Sub-Saharan Africa - Gries, Thomas; Kraft, Manfred; Meierrieks, Daniel (World Development)

The Optimal Distance to Port for Exporting Firms - Gries, Thomas; Naudé, Wim (Journal of Regional Science)

Explaining Regional Export Performance in a Developing Country: The Role of Geography and Relative Factor Endowments - Gries, Thomas; Naudé, Wim (Regional Studies)

Entrepreneurship and regional economic growth: towards a general theory of start-ups - Gries, Thomas; Naudé, Wim (Innovation: The European Journal of Social Science Research)

Studentische Modulevaluation - Methoden, Ergebnisse und Schlussfolgerungen aus statistischer Sicht - Lück, Sonja

Spieltheoretische Anmerkungen zur Förderung universitärer Spitzenforschung im Rahmen der Exzellenzinitiative - Kraft, Manfred; Brunn, Hans-Georg; Lück, Sonja (Bildungsökonomie in der Wissensgesellschaft)